Filters on computer displays -- effects on legibility, performance and comfort. - Sheedy JE; Subbaram MV; Hayes JR (Behaviour & Information Technology)
The hypothesis is that using a contrast-enhancing filter (CEF) on a computer display will improve display legibility, reading speed and visual comfort. Twenty subjects performed reading tasks, letter counting tasks, and legibility measurements on eight display conditions: a cathode ray tube (CRT) and liquid crystal display (LCD) matched for size and luminance - each at high luminance, with two different CEFs and a lower luminance to match one of the CEFs. The CEFs decreased both luminance and contrast when applied to the displays with the brightness set high, although the contrast was better with the filters compared to a matched luminance display without a filter. The legibility measurements support the positive effect of the CEFs due to improved contrast but the larger negative effect due to reduction in luminance results in a net loss of legibility. Performance on the reading and letter counting tasks was not improved with the CEFs.